Prospective, double-blind, randomized controlled trial of electrophysiologically guided femoral nerve block in total knee arthroplasty - Youm YS; Cho SD; Hwang CH (Dove Medical Press, 2013)
Yoon Seok Youm,1 Sung Do Cho,1 Chang Ho Hwang21Department of Orthopedic Surgery, 2Department of Physical Medicine and Rehabilitation, Ulsan University Hospital, University of Ulsan College of Medicine, Ulsan, Republic of KoreaBackground: The purpose of this study was to compare electrophysiologically guided and traditional nerve stimulator analgesia femoral nerve block after total knee arthroplasty.Methods: Patients scheduled for unilateral total knee arthroplasty were randomized to electrophysiologically guided or traditional nerve stimulator analgesia by pre-emptive single injection femoral nerve block with corresponding assistance. We assessed pain scores using a visual analog scale (VAS, 0 = no pain, 100 = the worst pain) and the volumes of morphine consumed at 4, 24, 48, and 72 hours after total knee arthroplasty.Results: Of the 60 patients enrolled, eight withdrew from the study. The remaining 52 patients were randomized to the electrophysiologically guided group (n = 27) or traditional nerve stimulator analgesia (n = 25) group. Four hours after total knee arthroplasty, VAS scores were significantly lower in the electrophysiologically guided group than in the traditional nerve stimulator group at rest (4.8 ± 1.4 versus 5.9 ± 0.8, P < 0.01) and while moving (6.2 ± 1.1 versus 6.9 ± 0.9, P < 0.01). The total volumes of morphine injected at 24, 48, and 72 hours were significantly decreased in the electrophysiologically guided group (P < 0.05 each). Variable × time interaction of VAS was significant in the electrophysiologically guided group (P < 0.05), with each VAS score at 24, 48, and 72 hours being significantly lower than the baseline score (P < 0.05). VAS scores at every time point were significantly lower in the electrophysiologically group guided than in the traditional nerve stimulator group (P < 0.05).Conclusion: Electrophysiologically guided single injection femoral nerve block may provide better postoperative analgesia and a greater reduction in the demand for pain killers than femoral nerve block using traditional nerve stimulator analgesia.Keywords: femoral nerve, nerve block, electrophysiologic concepts, arthroplasty, knee, ropivacaine